2018
DOI: 10.1039/c8sc00854j
|View full text |Cite
|
Sign up to set email alerts
|

Long distance ion–water interactions in aqueous sulfate nanodrops persist to ambient temperatures in the upper atmosphere

Abstract: The effect of temperature on the patterning of water molecules located remotely from a single SO42– ion in aqueous nanodrops was investigated for nanodrops containing between 30 and 55 water molecules using instrument temperatures between 135 and 360 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Another factor that may contribute to the high charging in our experiments is that droplets in vacuum undergo a "freeze-drying" effect where the droplet temperature is signicantly lowered by evaporative cooling. 53,54 This leads to a steady-state internal energy distribution that is substantially below the ambient temperature as the energy lost through evaporative cooling is replenished through gaseous collisions and absorption of blackbody radiation emitted from the surroundings. 55 The rate of water loss indicates that the temperature of these droplets must be substantially lowered.…”
Section: Origins Of Solution-dependent Nanodrop Mass and Chargementioning
confidence: 99%
“…Another factor that may contribute to the high charging in our experiments is that droplets in vacuum undergo a "freeze-drying" effect where the droplet temperature is signicantly lowered by evaporative cooling. 53,54 This leads to a steady-state internal energy distribution that is substantially below the ambient temperature as the energy lost through evaporative cooling is replenished through gaseous collisions and absorption of blackbody radiation emitted from the surroundings. 55 The rate of water loss indicates that the temperature of these droplets must be substantially lowered.…”
Section: Origins Of Solution-dependent Nanodrop Mass and Chargementioning
confidence: 99%
“…These results show that vibrational spectroscopy is a powerful tool to elucidate the structure of the water network surrounding the ionic core. Williams and co‐workers investigated how different core ions influence the hydrogen‐bond network in large water clusters up to n ≈550, far beyond the first solvation shell . They found that the free O−H band, resulting from the vibration of water molecules with at least one hydrogen atom not involved in hydrogen bonding, redshifts and increases in intensity with increasing positive charge .…”
Section: Introductionmentioning
confidence: 99%
“…Their work demonstrates long‐range solvation effects upon hydration of different ions. In a recent temperature‐controlled experiment with SO 4 2− (H 2 O) n , these ion–water interactions were seen at temperatures that are relevant to Earth's atmosphere . Thermochemical properties as well as infrared spectroscopic signatures have been frequently investigated as a function of cluster size to determine the transition to bulk‐like behavior of hydrated ions.…”
Section: Introductionmentioning
confidence: 99%
“…Microhydrated sulfate dianions, SO 4 2− (H 2 O) n , represent important model systems, since they are amenable to high level electronic structure calculations. [5][6][7][8][9] Blades and Kebarle reported the first mass spectrometric studies on gaseous SO 4 2− (H 2 O) n clusters. 5 They showed that at least three water molecules are necessary to stabilize the dianion, while smaller clusters are prone to either electron autodetachment or proton transfer and formation of HSO 4and OH -.…”
Section: Introductionmentioning
confidence: 99%
“…14 Photoelectron spectra of cold anions 15 as well as IRMPD spectra in the O-H stretching region 16 provided new insights, initially for n ≤ 7 and later also for clusters up to n = 80. 9,17,18 However, the structural assignments for individual cluster sizes remained controversial. For example, the structure of SO 4 2− (H 2 O) 6 was initially predicted to be of C 3 symmetry, 10 then T d symmetry 14 and later, a mixture of both isomers was proposed.…”
Section: Introductionmentioning
confidence: 99%